Assessment of reaction between thorium and polyelectrolyte nano-thin film using Box–Behnken design - Mahmoud Ali Asghar Aslani; Fatih Celik; Omer Mermer; Ceren Kutahyali Aslani (Adsorption Science & Technology)
Sandwich type polyelectrolyte nano-thin films (PENTFs) were prepared by using polyallylamine hydrochloride and polyacrylic acid from layer-by-layer assembly process with spin coating system. Their nanostructures have been studied by scanning electron microscope, atomic force microscope, and attenuated total reflectance Fourier transform infrared spectroscopy. In order to understand the effects of the initial concentration of thorium, initial solution pH, temperature, and contact time on the reaction between thorium and PENTF, an experiment data set was designed according to Box–Behnken model. The analysis of variance calculations for regression model were carried out in 95% confidence level and were checked for fitting experimental data and predicted values. The correlation coefficient value ( R 2 ) obtained as 94% showed that there was a correlation between the predicted and the observed values. The optimum pH, temperature, initial concentration of thorium, and interaction time in studied ranges were found as 2.81, 35℃, 160 mg·L −1 , and 120 min, respectively. At these conditions thorium (IV) ions adsorption yield was obtained as 89 ± 2%. The Freundlich, Langmuir, and Dubinin–Radushkevich isotherms were used to investigate the characteristics of the process. These characteristics data imply that the Freundlich model fits better than the Langmuir model for the Th (IV) sorption onto PENTFs with K F and n values were found to be 20.6 mg·g −1 and 1.08 L·mg −1 , respectively. The thermodynamic parameters were also computed as negative Δ H value suggest that adsorption of Th (IV) is exothermic nature. The calculated negative and positive values of Δ G indicate that the sorption process is favorable (energetically) while running below 40℃ and over this point the process status change to non-spontaneous, respectively.